Spatial Dynamics and Heterogeneity in the Cyclicality of Real Wages - Ziliak, James P.; Wilson, Beth A.; Stone, Joe A. (The Review of Economics and Statistics, 1999)
Neither the issue of how local and aggregate labor markets interact over time-nor the issue of how heterogeneity by education, race, and other factors interacts with these spatial dynamics-has previously been explored in the literature on the cyclicality of real wages. This study investigates how real wages respond to local and aggregate unemployment rates over time, and explores possible heterogeneities in the responses. Results, based upon data from the Panel Study of Income Dynamics, indicate that real wages move procyclically with both aggregate and local markets, but that the response to local changes occurs with a lag; that rates of return to education are procyclical overall for aggregate labor markets, but tend to be countercyclical for blacks; and that wages of union, manufacturing, blue-collar, and black workers tend to be less procyclical, even countercyclical for black college graduates. Overall, we find substantial spatial dynamics and heterogeneity in the cyclicality of real wages.